Conflict and Cultivation: How Boko Haram Activities Affect Soil Fertility in Some Locations from Gombi and Hong Local Government Areas of Adamawa State, Nigeria - Markus Joseph; Yusuf Ibrahim M.; Dauda Samaila (Darul Yasin Al Sys, 2026)
The study looks into the environmental degradation caused by Boko Haram's activities, with a particular focus on soil pollution in Adamawa State's Hong and Gombi Local Government Areas. It notes a lack of prior research on the insurgency's environmental impacts, which has primarily focused on security and governance. The study assessed the effects of Boko Haram on soil physicochemical properties, heavy metal concentrations, and crop safety for consumption, in comparison to a control site with no insurgent activity. Soil samples were collected from twelve villages, including Uba, Korlea, Mararaban Mubi, and others, at varying depths using a sampling auger. Heavy metals were analyzed using X-Ray Fluorescence Spectroscopy, and the data were statistically evaluated using ANOVA and Duncan's Multiple Range Test. Significant findings show that heavy metal concentrations vary with depth, with notable increases in iron and manganese, and that lead has a negative impact on soil health. The study emphasizes the risks that heavy metals such as cadmium and mercury pose to agricultural soils and human health, as well as global contamination issues affecting food safety. It advocates for natural bioremediation methods and emphasizes the importance of continuous monitoring and regulatory measures to reduce the risks associated with heavy metals in agriculture.